Construction of operation and maintenance management platform based on internet plus - Zhen YANG; Yanning CAO (Dianxin kexue)
At present,the application of E-government in China is getting more and more widespread.With the gradual increase of running online for business systems,the focus of technical support enterprises will shift their phases from system constructions to the operation and maintenance with the main features of deepening applications and improving response and disposal capabilities.In the new era,face boundary migration,weak early warning,complex troubleshooting,employee turnover and funds cutting etc.in system management,combined with the practice of the operation,several suggestions were put forward for the construction of “internet + operation ＆amp; maintenance” management platform in terms of such aspect as connection,innovation,openness and feedback of internet ,so as to further improve services level and efficiency for government affairs system.